2022
DOI: 10.2147/idr.s368444
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazinamide Resistance and pncA Mutation Profiles in Multidrug Resistant Mycobacterium Tuberculosis

Abstract: Purpose Pyrazinamide (PZA) is a critical component of standardized chemotherapy for tuberculosis (TB) and is recommended for the treatment of multidrug-resistant (MDR) TB. We aimed to characterize mutations in pncA of M. tuberculosis and evaluate their diagnostic accuracy for PZA susceptibility in China. We also combined genotypic methods with phenotypic susceptibility testing and pyrazinamidase (PZAse) activity to confirm PZA-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…During the study period, M. tuberculosis isolates in 19.0% (71/374) of participants were resistant to pyrazinamide, which is lower than 40% in the previous study conducted in Chinese patients with MDR-TB [ 9 ]. This may be attributed to the fact that more than 80% of the registered patients during this study were newly diagnosed and no previous usage of pyrazinamide may lead to a relatively lower resistance to pyrazinamide [ 18 ]. On the other hand, this study shows that the majority of patients with MDR-TB and M. tuberculosis isolates resistant to pyrazinamide have high-level MICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study period, M. tuberculosis isolates in 19.0% (71/374) of participants were resistant to pyrazinamide, which is lower than 40% in the previous study conducted in Chinese patients with MDR-TB [ 9 ]. This may be attributed to the fact that more than 80% of the registered patients during this study were newly diagnosed and no previous usage of pyrazinamide may lead to a relatively lower resistance to pyrazinamide [ 18 ]. On the other hand, this study shows that the majority of patients with MDR-TB and M. tuberculosis isolates resistant to pyrazinamide have high-level MICs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that pyrazinamide susceptibility is associated with better treatment responses [ 6 , 8 , 14 ]. However, the proportion of pyrazinamide resistance ranges from 10% to 85% among patients with MDR-TB in different geographic populations [ 15 , 16 , 17 , 18 ], which indicates the necessity of considering how to better use pyrazinamide.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazinamide (PZA) is a TB drug with a high bacteriocidal effect, because it can kill semidormant of M. tuberculosis (Shi et al, 2022;Shrestha et al, 2022).The efficacy of PZA as a TB drug is highly dependent on the action of the pyrazinamidase (PZase) enzyme encoded by the pncA gene of M. tuberculosis. As many as 80% of clinical isolates of PZA-resistant M. tuberculosis were reported to have pncA mutations (Khawbung et al, 2021;Lamont et al, 2020).…”
Section: Palavras-chave: Gene Pnca Mycobacterium Tuberculosis Resistê...mentioning
confidence: 99%
“…As many as 80% of clinical isolates of PZA-resistant M. tuberculosis were reported to have pncA mutations (Khawbung et al, 2021;Lamont et al, 2020). The types of mutations in the pncA gene were reported to be very diverse, and showed specificity in each geographic area where these clinical isolates were found (Hadi et al, 2023;Shi et al, 2022;Shrestha et al, 2022;Lamont et al, 2020;Purkan et al, 2016). M. tuberculosis strains that are defective in pncA thereby eliminating its PZase activity are reported to be resistant to PZA.…”
Section: Palavras-chave: Gene Pnca Mycobacterium Tuberculosis Resistê...mentioning
confidence: 99%
See 1 more Smart Citation